The ethics of welfare : human rights, dependency, and responsibility - Dean, Hartley, 1949- (Book collections on Project MUSE., 2004)
Present day policy makers endorse the cause of human rights, yet they tell us we can have no rights without responsibility and that dependency is irresponsible. This text offers a critique of this paradox and discusses the ethical conundrum it implies for the future of social welfare.